Synthesis and Antigiardial Activity of Formononetin Analogues (The East and Central African Journal of Pharmaceutical Sciences, 2019)
The synthesis and antigiardial activity of formononetin analogues is hereby reported. Formononetin, an isoflavone commonly obtained from the Leguminoseae family has previously been reported to possess antigiardial activity. In this paper, 10 analogues of formononetin were synthesized and tested for antigiardial activity. One compound was found to be active, 3 were moderately active and 6 were found to be inactive. All the 10 analogues were found to be inactive against other protozoa such as Trichomonas vaginalis and Tritrichomonas foetus.
Keywords: Antigiardial, Formononetin, Activity